2007
DOI: 10.1007/s10664-007-9036-6
|View full text |Cite
|
Sign up to set email alerts
|

Global and task effects in information-seeking among software engineers

Abstract: Information-seeking strategies were explored in software engineers. A complex interaction of task and geographic differences was revealed. There is a general tendency across software engineers to favor non-social sources, such as documentation, for tasks where the goal is to seek factual information. More social sources are preferred when seeking information to diagnostic, problem-solving questions. Within this effect, some geographic variations assert themselves in a way that might partly be interpreted in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…Similarly, Hertzum () found that the key selection factor for software engineers was appropriateness to task, and Fidel and Green () found that the second most important factor overall was can give data that meets the needs of the project . Further support for the importance of task‐appropriate information to software engineers was reported by Milewski () and Montesi and Navarrete (). Taken together, these studies suggest that situational, or task‐based relevance (Borlund, ), plays a major role in source‐selection decisions by software engineers.…”
Section: Related Literaturementioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, Hertzum () found that the key selection factor for software engineers was appropriateness to task, and Fidel and Green () found that the second most important factor overall was can give data that meets the needs of the project . Further support for the importance of task‐appropriate information to software engineers was reported by Milewski () and Montesi and Navarrete (). Taken together, these studies suggest that situational, or task‐based relevance (Borlund, ), plays a major role in source‐selection decisions by software engineers.…”
Section: Related Literaturementioning
confidence: 69%
“…However, more recent research has suggested that this principle does not adequately explain how engineers select from among available information sources. Alternate explanations include the role of trust, the challenges associated with finding information, the effect of different task types, cultural norms, and the richer opportunities for feedback and contextualization afforded by direct communication (Anderson et al, 2001;Hertzum, 2002;Hertzum, Anderson, Anderson, & Hansen, 2002;Hertzum & Pejtersen, 2000;Kwasitsu, 2003;Milewski, 2007).…”
Section: Related Literaturementioning
confidence: 99%
“…To the extent that team members can find, in a repository, everything they need to know in order to do their jobs, bridges become an unnecessary information channel. Nonsocial sources are often preferred for factual, predictable and highly specified information as well as more formal information that typically occurs at the beginning and end of a project (Milewski 2007). But even for an organization committed to repositing project information, it is difficult to do so for some kinds of information.…”
Section: Use a Bridge When There Is A High Need For Real-time Interacmentioning
confidence: 99%
“…Secondly, the nature of the task influences information seeking behaviour. Milewski (2007) found that during factual tasks, software engineers often consult documentary sources, whereas during diagnostic problem-solving tasks they consult social sources. In addition, Restrepo and Christiaans (2004) found that designers consult social sources during problem structuring activities and documentary sources during problem-solving activities.…”
Section: Introductionmentioning
confidence: 99%